Pengenalan Pola Berfikir Untuk Anak Sejak Dini - Sri Putrianingsih (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2020)
In this digital age, any human can tap into information for various access to modern technology. Even children, from an early age have access to all kinds of information through the social media. As parents, introduce your children to creative and positive thinking in order to use their leisure time to hone a brain with enjoyable activity. Children can play and learn to direct the interests and talents they have. Through the thought of children capable of socializing to others with good attitude. Parental assistance can help the children to explore more science than they have ever been able to get. Families, school, and good social environments strongly support children to raise their thinking levels, thus foster creativity on them.